Development and evaluation of a psycho-educational intervention program to enhance the psychological well-being of daughter and daughter-in-law caregivers of stroke survivors - Gholamzadeh, Sakineh (2013)
This study was aimed to develop, implement and evaluate a psycho-educational intervention program to enhance the psychological well-being (PWB) of daughter and daughter-in-law caregivers of severe ischemic stroke survivors after hospital discharge. The study followed an action research approach, which employed a collaborative cycle of reflection, re-planning, and taking action. The study includes four following steps: 1) exploration of caregiver needs and coping behaviors, 2)construction of the program, 3) action taking, and 4) randomized evaluation of the program. The data analysis from focused group and face to face interview revealed seven main categories that provided a perspective on daughters and daughters in-law needs and coping behaviors which includes: information and training, financial support, home health care assistance, self-care support, adjusting with the cultural imperative in providing care for a parent in-law, dissatisfaction with the health care system and needs for teaching problem-oriented coping approaches. There was no obvious theme specific to the type of relationship except cultural imperative in providing care for a parent in-law. In addition, content analysis of focus group interview with a panel of clinical and academic nurses revealed two major themes which include preventing burnout and information and training. Based on caregiver needs and nursing panel suggestion at phase І, literature review, and conceptual framework of the study a hospital-home transition program (HHTP) was established,validated, and modified with daughter and daughter in-law caregivers. After construction of the program, it was implemented to ensure acceptability and feasibility in a small sample of three caregivers. In the action research process, an individualized hospital-home based support program which consisted of seven sessions was implemented and evaluated in a larger sample (n=96) through a randomized sampling design. In the randomized study, the relationship between caregivers and stroke survivor’s demographics with PWB was examined at pre-intervention stage on a total sample of 96 caregivers to identify covariate variables. Only positive religious coping significantly affected caregivers’ psychological well-being. About 7.2% of changes in PWB can be explained by positive religious coping. Therefore, pre-intervention of the positive religious coping was used as the covariate in the next analysis. The results of the Mixed-ANCOVA revealed a statistical significant difference in psychological well-being score between intervention and control groups by time [F (1.45, 135.652) =8.53, p<0.01, η2 =0.084)] that showed the effectiveness of the new program. In addition, multi mediation analyses demonstrated that reductions in threat appraisal and increases in perceived preparedness (accounting for other mediators) mediated the effects of the intervention on psychological well-being. Intervention affected psychological well-being indirectly through changes in threat appraisal (β=0.1008 CIBCA=-0.0516–0.1726) and preparedness (β=0.0939 CIBCA=-0.0103–0.2044). The multiple mediator model accounted for 34.28% of the variance in the PWB change (p <0.001). These findings supported the mediating hypothesis for two of five hypothesized mediators. The results of this study would be a good starting point for focusing on the reasons for the success and or failure of intervention program by testing mediating factors in intervention studies.